PENERAPAN KOSAKATA DALAM MENULIS NASKAH PIDATO MAHASISWA SEMESTER IV PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA STKIP MPL - Kurniati, Lisdwiana (JURNAL PESONA, 2016)
The difficulties in speech text writing were faced by the students. They were confused inwriting the text creatively. It was indicated from the students less vocabulary then madethe students less writing. Studentsâ vocabularies such as synonym, antonym, andlanguage style were improving studentsâ skill in speech text writing. Through thosevocabularies, the students could choose and use it, then got good quality in writing.This research was reviewing vocabularies implementation in speech text writing. Theobjective of this research was studentsâ vocabularies in language skill activity throughspeech text writing.Key Words: speech text writing, vocabularies, language style